Health Workers Support, Culture and Status of Exclusive Breastfeeding in Sungai Ulin Community Health Center (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Exclusive breastfeeding is the most important nutrition for baby until 6 months old without any food or drinks addition. Based on Basic Health Research (Riskesdas) 2013, in Indonesia mother who exclusively breastfeeding her baby was still low only 38% while the government policy is targeting 80% in 2010. Furthermore, there was only 13,46% breastfeeding coverage in Sungai Ulin community health center in August 2015. The main factors that cause low exclusive breastfeeding coverage such as health worker support and culture of breastfeeding provision. The objective of this research is to determine correlation between health workers support and culture of breastfeeding with status of exclusive breastfeeding in the area of Sungai Ulin Community Health Center. This research used observational analytic method with case-control design, conducted in 2016. The sample in this study were mothers who have baby aged 6-12 months with 23 as cases (non-exclusive breastfeeding) and 46 as controls (exclusive breastfeeding) or the ratio of 1:2 was determined using the hypothesis test 2 proportion formula. The research used simple random samping technique using univariate and bivariate analysis with Chi-square test with 95% confidence level. The results showed there was correlation between health workers support (p-value = 0,013, OR = 6,271) and culture of exclusive breastfeeding provision (p-value = 0,0001, OR = 8,906) with status of exclusive breastfeeding.